PENYUSUNAN E-HANDOUT PENGAYAAN MATERI BIOPROSES SEL SEBAGAI BAHAN AJAR BIOLOGI SISWA SMA KELAS XI IPA - Awlia, Zahrotul; Febrianti, Novi (Bioilmi: Jurnal Pendidikan, 2023)
This study aims to determine the quality and feasibility of e-handout cell bioprocess materials as biology teaching materials for class XI IPA senior high school. The preparation of the e-handout uses the 4D development model which consists of define, design, develop and disseminate stages. The e-handout was validated by material expert validators, media experts and biology teachers. The e-handout that has been validated is then subjected to small-scale tests and large-scale tests to class XI IPA 4 students at SMAN 1 Jetis. The object of this research is the material enrichment e-handout for cell bioprocessing. Data collection techniques were carried out through product assessment questionnaires. Data from product assessment results are in the form of quantitative data which are analyzed descriptively qualitatively to determine the quality and feasibility of the e-handout. The results of the assessment showed that the quality of the e-handout from material experts got a percentage of 93.75% (very good category), media experts 80.21% (very good category) and biology teachers 96.87% (very good category). Small-scale test results get a percentage of 100% (very good category) and large-scale test 97.23% (very good category). Based on the results of this assessment, the prepared e-handout is suitable as biology teaching material for class XI IPA